TRAGEDI CHALLENGER (TINJAUAN ETIKA KANTIAN DAN ETIKA UTILITARIAN) - Sudaryanto, Sudaryanto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2015)
A lot of scientific experiments motivated by utilitarian attitudes. Experiments are expected to give satisfactory results or benefits. If an experiment has been carried out with the correct procedure, then the failure of an experiment is morally acceptable, because the nature of the experiments it is always a risk. The launch of the Challenger can be incorporated into the experimental category. Through the review process, engineering procedures and the launch of Challenger's failure status can be determined in terms of Kantian and Utilitarian ethics. The study is a research library, with a hermeneutic approach. The methodical elements used in this study are description, analysis, synthesis, and reflection. The results of this study indicate that the engineering procedures and Challenger launch decision to ignore the real risks are taken into account technically. Therefore, the failure of the Challenger mission in terms of Kantian and Utilitarian ethics can not be accepted.